Effect of cationic and anionic dye adsorption by base-modified papaya seed (fixed-bed system) / Norhaslinda Nasuha, Nurulhuda Amri and Hawaiah Imam Maarof - Nasuha, Norhaslinda; Amri, Nurulhuda; Imam Maarof, Hawaiah (Universiti Teknologi MARA Pulau Pinang, 2014)
Fixed-bed adsorption studies were conducted to evaluate the efficiency of Modified Papaya Seeds (MPS) and Natural Papaya Seeds (NPS) as adsorbents for the removal of Methylene Blue (MB) and Congo Red (CR) from aqueous solution under the effect of various process parameters namely bed depth (15- 30 mm), flow rate (15-35 mL/min) and initial concentrations (15-35mg/L). The results showed that the total adsorbed quantities and equilibrium uptake decreased with increasing flow rate and increased with increasing initial MB and CR concentration. Breakthrough time and exhaustion time increased with increasing bed depth.